184k views
8 votes
Please help please...

Please help please...-example-1
Please help please...-example-1
Please help please...-example-2

1 Answer

7 votes

first part: put them equal to each other

6x - 25 + 4x = 45 + 3x - 7

10x - 25 = 38 + 3x

7x - 25 = 38

7x = 63

x = 9

second part: plugin

6x - 25 + 4x

6(9) - 25 + 4(9)

54 - 25 + 36

29 + 36

= 65

-- plugging this in one of the equation is enough, since both are the same.

final answer for the second part: 65

User AlexanderN
by
5.5k points